UJI PENGARUH SALIVA BUATAN TERHADAP KEKUATAN TEKAN SEMEN IONOMER KACA TIPE II YANG DIRENDAM DALAM MINUMAN ISOTONIK - Fitriyana, Dwi Cahya; Pangemanan, D. H. C.; ., Juliatri (Universitas Sam Ratulangi, 2014)
Abstract: The immersion of GIC type II in acid drink like isotonic drink could reduce the compressive strength (CS) of GIC type II. This is due to the matrix degradation process of GIC in acid condition. But on the other hand, there is artificial saliva that can neutralize this condition. Purpose: Purpose of this study was to evaluate the effect of artificial saliva on compressive strength of GIC type II immersed in isotonic drink. Method: The GIC specimens of 6mm x 6mm x 12mm (length x width x depth) were immersed for 24 hours in water, 24 hours in isotonic drink, 24 hours in isotonic drink and continue with 72 hours in artificial saliva, 48 hours in isotonic drink, and 48 hours in isotonic drink and continue with 144 hours in artificial saliva. The compressive strength was determined using Universal Testing Machine with a crosshead speed of 0.5 mm/min. Statistical analysis was performed by one-way ANOVA and post-hoc LSD test ( = 0.05). Result: Statistic test shows significant difference of CS (p<0,05). Conclusion: conclusion of this study artificial saliva gives effect to the rising of the compressive strength of GIC type II immersed in isotonic drink. Keywords: Isotonic drink, artificial saliva, compressive strength, Glass Ionomer Cement type II. Abstrak: Perendaman SIK tipe II dalam minuman asam seperti minuman isotonik dapat mengurangi kekuatan tekan SIK tipe II. Hal ini disebabkan proses degradasi matriks SIK pada kondisi asam. Namun di sisi lain, saliva buatan yang dapat menetralkan kondisi ini. Tujuan: untuk untuk mengetahui pengaruh saliva buatan terhadap kekuatan tekan SIK yang direndam dalam minuman isotonik. Metode: Spesimen SIK tipe II berukuran 6mm x 6mm x 12 mm (panjang x lebar x tinggi) direndam selama 24 jam dalam air, 24 jam di dalam minuman isotonik, 24 jam di dalam minuman isotonik dan lanjutkan dengan 72 jam pada saliva buatan, 48 jam di minuman isotonik, dan 48 jam di minum isotonik dan lanjutkan dengan 144 jam dalam saliva buatan. Kekuatan tekan diukur menggunakan Universal Testing Machine dengan kecepatan 0,5 mm / min. Analisis statistik dilakukan dengan one-way ANOVA dan post-hoc uji LSD ( = 0,05). Hasil: Uji statistik menunjukkan perbedaan yang signifikan dari kekuatan tekan (p <0,05). Simpulan: terdapat pengaruh saliva buatan terhadap kekuatan tekan SIK tipe II yang direndam dalam minuman isotonik. Kata kunci: minuman isotonik, saliva buatan, kekuatan tekan, Semen Ionomer Kaca tipe II.